A 15.6 frames per second 1‐megapixel multiple exposure laser speckle contrast imaging setup. Issue 2 (7th August 2017) - Hultman, Martin; Fredriksson, Ingemar; Larsson, Marcus; Alvandpour, Atila; Strömberg, Tomas
Abstract : A multiple exposure laser speckle contrast imaging (MELSCI) setup for visualizing blood perfusion was developed using a field programmable gate array (FPGA), connected to a 1000 frames per second (fps) 1‐megapixel camera sensor. Multiple exposure time images at 1, 2, 4, 8, 16, 32 and 64 milliseconds were calculated by cumulative summation of 64 consecutive snapshot images. The local contrast was calculated for all exposure times using regions of 4 × 4 pixels. Averaging of multiple contrast images from the 64‐millisecond acquisition was done to improve the signal‐to‐noise ratio. The results show that with an effective implementation of the algorithm on an FPGA, contrast images at all exposure times can be calculated in only 28 milliseconds. The algorithm was applied to data recorded during a 5 minutes finger occlusion. Expected contrast changes were found during occlusion and the following hyperemia in the occluded finger, while unprovoked fingers showed constant contrast during the experiment. The developed setup is capable of massive data processing on an FPGA that enables processing of MELSCI data in 15.6 fps (1000/64 milliseconds). It also leads to improved frame rates, enhanced image quality and enables the calculation of improved microcirculatory perfusion estimates compared to single exposure time systems. Abstract : Multiple exposure time laser speckle contrast blood flow images (MELSCI) are recorded using a 1‐megapixel camera running at 1 kHz. Synthetic multiple exposure time (1‐64 milliseconds) contrast images are calculated in real‐time using a field programmable gate array. The low noise MELSCI system can lead to improvements in healthcare for people suffering from impaired blood flow in the microcirculation.